INDICATION OF VEDIC PLANTS AVAILABLE IN THE PRESENT ERA - Kalpana, *Rajam Mahendra; Sitaram, Bulusu (International Journal of Ayurveda and Pharma Research, 2016)
Vedas which are four in number are actually derived from the voice of Lord Brahma deva heard by our ancient Rishis. They contain hymns about the many forms of Omnipotent Lord of the universe. In Vedas, many references are available on many plants which are used in rituals, sacrifices and medicines. Many common and rare diseases were treated with the help of these plants. Some plants mentioned in Vedic literature are known with the same name even today and are under continuous utility since that period. Their therapeutic values are boundless and amazing. As all these plants are native to our country they are available readily in our near vicinity. Many plants have been mentioned in the Vedic literature. Some of them are Prishni parni, Shami, Udumbara, Apamarga, Ashikni, Aswattha, Rajani and Nyastika. Fifteen plants which are known for the therapeutic value and are easily available are studied and enumerated for their therapeutic values in the Vedic literature, Ayurvedic and latest scientific literature. Comparision of the therapeutic uses from the Vedic literature to the ayurvedic literature is done and studied the similarities and differences. It is found that for most of the plants, the therapeutic uses are similar from the Vedic and Ayurvedic literature. This study helps to compare the past and present indications of Vedic plant drugs. Some new indications are found to be promising to pave a perfect way to cure some modern diseases also.